(3SQM GdYHhf aj TQM QSGdI GHf RjOhfs - (3eMeO Hf eMeO Hf eMeO Hf GdMSf GdLPGej GdaGQbj GdeUQj, GHf fHGJg , LeGd GdOjf CHh HcQ,J (B768 (3g` s; (3GHf fHGJI , eMeO Hf eMeO Hf eMeO Hf GdMSf GdLPGej GdaGQbj GdeUQj, LeGd GdOjf CHh HcQ,J (B768 (3g` s ((3CHhYhV YHOGdQMef s)
(3ChdgG (B:s
(3hHYO aEfi GeQJ HTQM QSGdI GdhRjQ CHj GdhdjO Hf RjOhf GdCJi PcQgG , hGjVGM HQGgjfgG GdZGeV Ydi cKjQ ef SQGg GdOH SQgG s
(3BNQgG (B:s
(3YWQ Gddg HPcQg GdeTGQb hGdeZGQH hRjf SeGM GdeOM ef efGbHg HRjfI GdchGcH hdGCNdi CHhGH fYeg hYdeg s
(3fSNI KGfjI ai ChdgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGX s
(3YdjgG HYV GdJUMjMGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs